2015
DOI: 10.1371/journal.pone.0142208
|View full text |Cite
|
Sign up to set email alerts
|

Complex Evolutionary and Genetic Patterns Characterize the Loss of Scleral Ossification in the Blind Cavefish Astyanax mexicanus

Abstract: The sclera is the tough outer covering of the eye that provides structural support and helps maintain intraocular pressure. In some fishes, reptiles, and birds, the sclera is reinforced with an additional ring of hyaline cartilage or bone that forms from scleral ossicles. Currently, the evolutionary and genetic basis of scleral ossification is poorly understood, especially in teleost fishes. We assessed scleral ossification among several groups of the Mexican tetra (Astyanax mexicanus), which exhibit both an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(97 citation statements)
references
References 47 publications
6
91
0
Order By: Relevance
“…This hybridization likely explains the variability in ossicle number observed in our samples, although a previous study of laboratory‐reared Chica individuals found no evidence for scleral ossicles in this group (O'Quin et al, ). Although the average size of many of these samples was below common length (data not shown), suggesting that individual differences in growth could account for these differences ossicle number (Franz‐Odendaal et al ., ; O'Quin et al, ), we found that body size accounted for only 45% of the variation in scleral ossicle number among these individuals. In addition, at the sizes sampled (4.3 cm on average), both ossicles, if present, should have started to ossify (Franz‐Odendaal et al, ); and, indeed, we found above average sized individuals with 0, 1, and 2 ossicles, suggesting that some of the variation in ossicle number found among these individuals is indeed genetic.…”
Section: Discussionmentioning
confidence: 60%
See 4 more Smart Citations
“…This hybridization likely explains the variability in ossicle number observed in our samples, although a previous study of laboratory‐reared Chica individuals found no evidence for scleral ossicles in this group (O'Quin et al, ). Although the average size of many of these samples was below common length (data not shown), suggesting that individual differences in growth could account for these differences ossicle number (Franz‐Odendaal et al ., ; O'Quin et al, ), we found that body size accounted for only 45% of the variation in scleral ossicle number among these individuals. In addition, at the sizes sampled (4.3 cm on average), both ossicles, if present, should have started to ossify (Franz‐Odendaal et al, ); and, indeed, we found above average sized individuals with 0, 1, and 2 ossicles, suggesting that some of the variation in ossicle number found among these individuals is indeed genetic.…”
Section: Discussionmentioning
confidence: 60%
“…Although this distinction is subtle, we believe it is important for three reasons. First, this result was unexpected based on previous results that found only individuals with zero scleral ossicles from this cave (n = 3; O'Quin et al, ), suggesting that further sampling among additional populations may be useful for uncovering additional variation. Second, it was unexpected given our hypothesis that intraspecific variation would be limited by the epistatic nature of the genes that control scleral ossification which favors the presence of scleral ossicles (O'Quin et al, ; Lyon et al, ), suggesting that this epistasis has been overcome by considerable backcrossing, which is consistent with previous reports of introgression of cavefish alleles in this population (Strecker et al, ; Gross, ).…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations